2015
DOI: 10.56189/ja.v4i1.199
|View full text |Cite
|
Sign up to set email alerts
|

MORFOLOGI BUNGA YANG SESUAI BAGI KULTUR MIKROSPORA PADA TANAMAN JARAK PAGAR (Jatropha curcas L.)

Abstract: An experiment aimed in gaining information on morphological characteristics of Jatropha curcas (L.) containing high frequency of uninucleate microspores has been done. This was important due to the successful application of experiment in haploid technique through anther or microspore culture is strongly determined by the availability of information from basic research such as appropriate morphology of the flowers. This scientific article, in our knowledge, was an early explanation of the initial steps of whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Figure 2 shows the learning curve of shooting in terms of shooting accuracy and precision. According to Pritasari, et al (2013) and Suaib (2011), repeated-measures ANOVA can analyze a research variable that is observed repeatedly at different times or periods. Based on the results (Table 2), there was a significant increase in the accuracy of regular shooters [F (4.44) = 11.253; p = 0.000] and expert shooters [F (4.44) = 18.738; p = 0.000].…”
Section: Figure 2 Shooting Accuracy and Precision For Regular And Exp...mentioning
confidence: 99%
“…Figure 2 shows the learning curve of shooting in terms of shooting accuracy and precision. According to Pritasari, et al (2013) and Suaib (2011), repeated-measures ANOVA can analyze a research variable that is observed repeatedly at different times or periods. Based on the results (Table 2), there was a significant increase in the accuracy of regular shooters [F (4.44) = 11.253; p = 0.000] and expert shooters [F (4.44) = 18.738; p = 0.000].…”
Section: Figure 2 Shooting Accuracy and Precision For Regular And Exp...mentioning
confidence: 99%